Implementasi Pembinaan Akhlak Peserta Didik Melalui Pembiasaan Shalat Dhuha dan Shalat Dzuhur Berjama’ah - Sopwandin, Iwan (Sekolah Tinggi Agama Islam (STAI) Al Hidayah Tasikmalaya, 2025)
The habit of praying Dhuha and Dzuhur in congregation also has a positive impact on the development of students' spirituality. Prayer as one of the main worships in Islam, can provide inner peace and coolness of soul for anyone who performs it with full devotion. By performing worship regularly, students will feel closer to Allah SWT, and gain peace in living their daily lives, both in school and outside of school. This study aims to analyze the implementation of moral development of students through the habit of praying Dhuha and Dzuhur in congregation at Al-Hidayah Islamic High School Cukangkawung Sodonghilir Tasikmalaya. The method used in this study is qualitative with a descriptive analysis approach. The data collection techniques are through observation, interviews, and documentation studies. While the data analysis technique uses the interactive Miles and Huberman model consisting of data condensation, data presentation and drawing conclusions, as well as for data validity testing through observation diligence, triangulation, reference adequacy, and member checks. The results of this study indicate that the habituation activities of praying dhuha and dzuhur in congregation at SMA Islam Al-Hidayah Cukangkawung Sodonghilir Tasikmalaya are carried out in a programmed and planned manner. With steps starting from habituation carried out since students enter grade X, habituation is carried out continuously, and habituation is monitored strictly, consistently, and firmly. This habituation has implications for students including spiritual, social, educational, school environment, psychological, and academic achievement aspects